(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2018)
Only 6 East African countries and 15 years (1996-2010) macroeconomic data was considered due limitation of data availability. Secondary data sources was used and necessary data were collected from the World Bank Development Indicator, Food and Agricultural Organization of the United State, and International Monetary fund base line data. Both descriptive and econometric models were employed. A Demand and Supply Linear Model was employed for the analysis. The selection test result confirmed that random effect to be an appropriate model for the analysis. Findings of the study revealed that the supply side of Agricultural Product Export were found to be statistically significant at P< 0.01 level, while the demand side Ln Growth Domestic Product of China variables was found to be statistically significant at P< 0.01. Int. J. Agril. Res. Innov. & Tech. 8 (2): 54-60, December, 2018